Tinjauan Sistematis dan Meta-Analisis: Analisis Dampak Intervensi Apoteker terhadap Clinical Outcome Pasien Epilepsi - Najmah Salsabila; Jason Merari Peranginangin; Dian Marlina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
People with epilepsy generally experience impaired social contact and decreased health. The role of pharmacists in the implementation of therapy for epilepsy patients is very important in providing pharmaceutical services. This research was conducted to examine the impact of pharmacist intervention on the clinical outcome of epilepsy patients. The research method was a systematic review and meta-analysis with a randomized controlled trial study design. Articles were obtained through electronic databases such as PubMed, Directory of Open Access Journals (DOAJ), SpringerLink, ScienceDirect, and Wiley. Items were selected using the PRISMA flowchart. Articles were analyzed using Review Manager 5.3. The results obtained were 10 articles from various countries, namely England, Singapore, China, Thailand, Colombia, America, and Nigeria. The data obtained showed that the pharmacist's intervention had a positive impact by increasing the clinical outcome of epilepsy patients compared to the absence of a pharmacist (SMD = 0.56; 95% CI = 0.03 to 1.10; p = 0.04). Then there was high heterogeneity (I2) between experiments (I2 = 96%; p <0.001), this was due to the different population variations. Furthermore, from the results of merging these 10 articles, it was found that there was publication bias as seen from the funnel plot graph which looked asymmetrical between the right and left plots. The interventions provided by pharmacists, namely consultation and counseling proved to have a positive impact on the clinical outcome of epilepsy patients in the form of increasing quality of life by decreasing seizure frequency and increasing knowledge of epilepsy patients.